An Oligosaccharide Rich Diet Increases Akkermansia spp. Bacteria in the Equine Microbiota - Lindenberg, Frederikke Christine; Lützhøft, Ditte Olsen; Krych, Lukasz; Fielden, James; Kot, Witold; Frøkiær, Hanne; van Galen, Gaby; Nielsen, Dennis Sandris; Hansen, Axel Kornerup (Frontiers in Microbiology, 2021)
Some oligosaccharides induce growth of anti-inflammatory bacterial species and induce regulatory immunity in humans as well as animals. We have shown that the equine gut microbiota and the immune-microbial homeostasis largely stabilize within the first 50 days of life. Furthermore, we have previously established that certain bacterial species in the equine gut correlated with regulatory immunity. Accordingly, we hypothesized that an oligosaccharide rich diet fed to foals during the first 50 days would increase the abundance of bacterial species associated with regulatory immunity, and that this would influence immune responses in the foals. Eight pregnant mares and their foals were fed an oligosaccharide rich diet from four weeks before expected parturition until 49 days post-partum. Six mares and foals served as control. Fecal microbiota from mares and foals was characterized using 16S rRNA gene amplicon high throughput sequencing. On Day 49 the test foals had significantly higher abundances of Akkermansia muciniphila and an unclassified Akkermansia spp.. Blood sampled from the foals on Day 7, 28 and 49 showed non-significant increases in IgA, and decreases in IgG on Day 49. In BALB/cBomTac mice inoculated with gut microbiota from test and control foals we found increased species richness, increased relative abundance of several species identified as potentially anti-inflammatory in horses, which were unclassified Clostridiales, Ruminococcaceae, Ruminococcus, Oscilospira and Coprococcus. We also found increased il10 expression in the ileum if inoculated with test foal microbiota. We conclude that an oligosaccharide diet fed to foals in the “window of opportunity”, the first 50 days of life, increases the abundance of anti-inflammatory species in the microbiota with potentially anti-inflammatory effects on regulatory immunity.